Anesthesia in a pediatric patient with Xeroderma pigmentousoma: A case report - Karami, Tohid; Abbaszadeh, Mohammad; Ghaffarizadeh, Farzaneh (Iranian Journal of Pediatric Surgery, 2019)
Xeroderma pigmentosum (XP) is an autosomal recessive genetic disorder with the following conditions: neurologic disorders that gradually progress and skin hypersensitivity to ultraviolet (UV). Inhalational anesthetic drugs should be avoided in these patients since they may induce DNA damage, also use of muscle relaxants should be kept to a minimum. Thus for XP patients, total intravenous anesthesia (TIVA) is more appropriate for inducing general anesthesia and airway manipulation must be kept to a minimum. We report a 6 year old boy with XP and its airway management and anesthesia during surgery